Specific feedback makes medical students better communicators - Engerer, Cosima (BMC medical education, 2019)
Background: Feedback is regarded a key element in teaching communication skills. However, specific aspects of feedback have not been systematically investigated in this context. Therefore, the aim of this study was to investigate the effectiveness of communication skills training (CST) integrating specific, structured and behavioral feedback. Methods: We condensed best practice recommendations for feedback in a CST for undergraduate medical students and compared the effect of specific, structured and behavior-orientated feedback (intervention group CST-behav) to general, experience-orientated feedback (CST- exp. as our control group) in a randomized controlled trial (RCT). We investigated changes on communication skills evaluated by independent raters, and evaluated by standardized patients (SP). To do that, every student was video-recorded in a pre and post assessment. Results: Sixty-six undergraduate medical students participated voluntarily in our study. Randomization did not result in equally skilled groups at baseline, so valid inter-group comparisons were not possible. Therefore, we analyzed the results of 34 students of our intervention group (CST-behav). Five out of seven domains in communication skills as evaluated by independent raters improved significantly, and there was a significant change in the global evaluation by SP. Conclusions: Although we were unable to make between-group comparisons, the results of the within group pre-post evaluation suggest that specific feedback helps improve communication skills.
Gesehen am 02.08.2019